Effectiveness of Use of Historical Learning Media Based on Mobile Learning in Increase Awareness of History of Students at SMAN 1 Sumberejo - Meihan, Andre Mustofa (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
Education in this era requires technology as a supporting facility in facilitating the learning process. Based on observations made at SMA Negeri 1 Sumberejo, it was found that the history learning media used was simple, and the learning was still teacher-centered. Monotonous subject matter and teaching concepts that only memorize textbooks make students lazy to study. This problem affects students' historical awareness. The historical awareness of students at SMAN 1 Sumberejo is still low, as evidenced by the results of the distribution of students' historical awareness questionnaires in class X IPS of SMAN 1 Sumberejo, which obtained an average score of only 63.05 or around 42.03%. This study aims to determine how effective mobile learning-based history learning media is in increasing students' historical awareness at SMAN 1 Sumberejo. The method used in this research is the experimental research method. Based on the discussion results, it can be concluded that using mobile learning-based historical learning media at SMAN 1 Sumberejo has proven effective in increasing students' historical awareness. This conclusion is based on hypothesis H0 is rejected, and H1 is accepted because the independent sample t-test obtained a sig of 0.000. Or the t value has a significance level (2-tailed) < (0.05).